2024
DOI: 10.1287/mnsc.2021.03746
|View full text |Cite
|
Sign up to set email alerts
|

Stepping Sideways to Step up: Lateral Mobility and Career Advancement Inside Organizations

Matthew Bidwell,
J. R. Keller

Abstract: Although internal labor market theory emphasizes promotions as the main form of mobility within organizations, many internal job moves take people sideways into jobs that are at the same hierarchical level as the one that was left. Despite the prevalence of these lateral moves, however, we have little evidence on what role they play in workers’ careers. We argue that lateral mobility can facilitate subsequent career advancement by allowing for the development and demonstration of new skills and can, therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Additionally, Mobley et al (1978) and Lambert et al (2006) found that job satisfaction has a significant impact on turnover intention and perceived job availability is also associated with turnover intention. If an organization fails to offer substantial prospects for internal development, employees who aspire for personal growth may proactively seek alternative opportunities in the external job market (Bidwell & Keller, 2024;Jiang et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, Mobley et al (1978) and Lambert et al (2006) found that job satisfaction has a significant impact on turnover intention and perceived job availability is also associated with turnover intention. If an organization fails to offer substantial prospects for internal development, employees who aspire for personal growth may proactively seek alternative opportunities in the external job market (Bidwell & Keller, 2024;Jiang et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%